An Analysis of Anti-Fat Bias LibGuides: Are Libraries in the Thick of It? - Christie Silkotch; Laura Haines; Amalia Dolan (Evidence Based Library and Information Practice)
Objective – This research investigates library research guides that share information about anti-fat bias to support weight-inclusive education or practice. By analyzing these guides, we seek to understand how academic librarians are engaging in this work and how they can continue to support weight inclusivity as educators, proponents of information literacy, and interdisciplinary partners.